210k views
0 votes
For questions 7 – 8, use the following functions: f(x) = 4x + 3x g(x) = 2x – 5 7. Find (f + g)(x). 8. Find (f – g)(x).

For questions 7 – 8, use the following functions: f(x) = 4x + 3x g(x) = 2x – 5 7. Find-example-1

1 Answer

1 vote

Answer:

7) (f+g) (x) = 4^x + 5x -5

8) (f-g) (x) = 4^x + x - 5

Explanation:

7) Find (f +g)(x)

(4^x + 3x + 2x - 5)

(4^x + 5x -5)

(f+g) (x) = 4^x + 5x -5

8) Find (f-g)(x)

(4^x + 3x - 2x - 5)

(4^x + x - 5)

(f-g) (x) = 4^x + x - 5

User Rashok
by
5.9k points